Mauritius - Report on the Observance of Standards and Codes (ROSC): Accounting and Auditing - World Bank (World Bank, Washington, DC, 2013)
The second Report on the observance of standards and codes (ROSC) Accounting and Auditing (A&A) review in Mauritius aims to determine what reforms should be undertaken to further strengthen the accountancy institutional framework that is critical in contributing to the country's economic growth. In 2010, the Government of Mauritius invited the World Bank to conduct this follow-up review. The first ROSC A&A was carried out in 2003. The new review establishes the extent of implementation of the 2003 policy recommendations and also identifies emerging strengths and weaknesses in institutional framework that underpin accounting and auditing practices that influence the quality of financial reporting. Further policy recommendations in this ROSC address the identified systematic weaknesses. Ultimately, if implemented, the recommendations would improve corporate financial reporting that will enhance Mauritius' business environment and advance its governance and financial accountability both key contributors to improving investor confidence and attracting investments. The ROSC A&A review team used a diagnostic template developed by the World Bank to facilitate collection of data. The data was complemented by the findings of a due diligence exercise obtained by the team during a series of meetings held with key stakeholders. During the meetings, the team also obtained information on the status of implementation of 2003 recommendations. A National steering committee comprising representatives of stakeholders in the accounting and auditing community in Mauritius supported the ROSC team.